Effect of five inclusion levels of mulberry (Morus alba cv. cubana) on methanogens and some main cellulolytic populations within rumen liquor of water buffalos (Bubalus bubalis) - González, Niurka; Abdalla, Adibe L.; Galindo, Juana; Santos, María Regina; Louvandini, Patricia; Louvandini, Helder (Cuban Journal of Agricultural Science, 2016)
In order to study the effect of five inclusion levels of mulberry (Morus alba cv. cubana) on methanogens and some main cellulolytic populations within rumen liquor of water buffalos (Bubalus bubalis), and contribute to the knowledge of the action mechanism by which the Cuban variety of mulberry reduces ruminal methanogenesis, an in vitro fermentation was carried out and five inclusion levels (0, 15, 20, 25 and 30%) of M. alba vc. cubana to a diet based on star grass (Cynodon nlemfuensis) were evaluated. Total, methanogenic and cellulolytic (Fibrobacter succinogenes, Ruminococcus albus) bacteria, and fungi were identified and quantified by polymerase chain reaction in real time. The percentage of cellulolytic and methanogenic bacteria, regarding total bacteria population was evaluated, as well as the delta delta Ct (ΔΔCt) and the expression of different ruminal microbial populations, in relation to control treatment. The inclusion of M. alba cv. cubana did not affect the studied ruminal microbial populations. The percentage of representation of F. succinogenes, R. albus and methanogens, regarding total bacteria was not affected with the inclusion of this variety of mulberry on the diet. Values of ΔΔCt and expression relative to control treatment of microbial populations evidenced that diets containing mulberry tree had the same difference and the same expression relative to the control treatment. It can be concluded that inclusion of M. alba cv. cubana on diet not affect the main microbial populations that degrade the fiber in the rumen, which could be used as a strategy for reducing methane production in the rumen. The mechanism by which this plant is able to reduce ruminal methanogenesis is not through direct effect on methanogens. Key words: mulberry, cellulolytic microorganisms, real time polymerase chain reaction, methane, rumen